New Polygonal Hysteretic Model for Simulation of Superelasticity Effect of Shape Memory Alloys - Todorov, Koce; Petkovska Oncevska, Svetlana (Society for materials and structures testing of Serbia, 2012)
The term shape memory alloys (SMA) refers to the group of metallic materials that demonstrate the ability to return to the same predefined shape or size when exposed to an appropriate thermal procedure. The unique characteristics of SMA, i.e., the high damping capacity, the high level of stress and strains recovery, the re-centring capabilities and the high corrosion resistance make this material attractive for scientific research. This paper shows the general characteristics of the shape memory alloys and the main physical-mechanical properties of the most frequently used commercial alloys. Definition of a material model for numerical simulation of the superelastic response of shape memory alloys is very important for their mathematical modelling. For that purpose, a new original polygonal hysteretic model with variable tangent stiffness has been developed for description of the superelasticity effect in the case of cyclic axial loading The model has a number of advantages as are the simple algorithm for computation, the easy definition of the necessary material parameters by means of a uniaxial compressive or tension test, the different elastic characteristics in the austenite and martensite phase, the possibility of simulation of different loading conditions at cyclic loading and the easy implementation in some of the open software codes.
Keywords: shape memory alloys, superelasticity, hysteretic model